Perioperative Management of Tonsillectomy in Pediatrics with Tetralogy of Fallot - Rizqi Ahmad Nur Dwiyono; Paramita Putri Hapsari (Journal of Anesthesiology and Clinical Research, 2022)
Introduction. Tetralogy of Fallot (TOF) is a cyanotic congenital heart disease that includes ventricular septal defect, aortic overriding, infundibular stenosis, and Right Ventricle Hypertrophy (RVH). Perioperative management includes preoperative management, intraoperative anesthesia, and post-operative and potential problem management. Case presentation. We report a -8-year-old-girl with congenital heart disease TOF planned for tonsillectomy and adenoidectomy. The patient weighs 18 kilograms, has a blood pressure of 96/55 mmHg, pulse rate of 104 times per minute, respiratory rate 24 times per minute, and oxygen saturation of 74-79% supine position with room air. We find ejection systolic murmur at SIC 4/6 left parasternal and clubbing fingers-on physical examination. Laboratory preoperation shown Hb value 22.9; Hct : 70; AL : 11.2; AT : 281; AE : 8.58. We pre-medicate with ondansetron, dexamethasone, and sedation in the transit room with ketamine and midazolam. Induction by fentanyl and rocuronium to facilitate endotracheal intubation. Postoperatively, the patient was transferred to the PICU with an ET in a tube. She is monitored for a post-operative complications such as active bleeding to hyper cyanotic and performed extubation less than 24 hours after surgery. Conclusion. Anesthetic goals in this patient are to maintain or slightly increase the Systemic Vascular Resistance, minimize Pulmonary Vascular Resistance dan provide mild cardiac depression.